Ultra-high performance concrete suitable for a vibrating environment, and a method of manufacturing and use thereof

By combining Fe-Mn-Si type shape memory alloy fibers and epoxy-amine modified acrylate emulsion, ultra-high performance concrete suitable for vibration environments is formed, which solves the problem of poor damping performance of traditional ultra-high performance concrete in extreme vibration environments, and achieves a synergistic effect of high strength, high toughness and high damping, and has self-healing ability.

CN121063885BActive Publication Date: 2026-01-23SHIJIAZHUANG TIEDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511630386.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-01-23
Estimated Expiration
2045-11-10

AI Technical Summary

Technical Problem

Traditional ultra-high performance concrete has poor damping performance in extreme vibration environments, is prone to fatigue failure, and is difficult to balance high strength and high toughness.

Method used

By combining Fe-Mn-Si shape memory alloy fibers and epoxy-amine modified acrylate emulsions, a synergistic system of macroscopic energy dissipation and microscopic damping is formed through chemical bonding. The vibration energy is dissipated by the phase transformation recovery force of the shape memory alloy and the chemical bonding interface reaction, thus preparing ultra-high performance concrete suitable for vibration environments.

Benefits of technology

It achieves a balance of high strength, high toughness, and high damping performance, improving the dynamic stability and durability of the material under extreme vibration environments, and possessing self-healing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121063885B_ABST
    Figure CN121063885B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and particularly relates to a kind of ultra-high performance concrete suitable for vibration environment and a preparation method and application thereof. The ultra-high performance concrete provided by the application comprises a reference component, an A component and a B component. The reference component has a mass ratio of cement:silica fume:quartz sand:water reducing agent:water = 65-75:18-22:90-110:2-3:17-19. The volume content of the A component is 1.0-2.0% of the total volume of the ultra-high performance concrete. The volume content of the B component is 2.5-4.0 times of the volume of the A component in terms of solid content. The A component and the B component are covalently bonded through an epoxy-primarily amino interface to form a strong interface. The B component consumes initial energy through molecular chain friction. The A component consumes secondary energy through phase change restoring force and inhibits cracks. The A component and the B component are combined to realize the unification of high strength, high toughness and high damping.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of building materials, and particularly relates to a super high performance concrete suitable for a vibrating environment and a preparation method and application thereof. BACKGROUND

[0002] In extreme vibrating environments such as nuclear power facilities, precision instrument platforms, large-span bridge seismic components, high-speed railway sleepers, etc., high requirements are put forward for the dynamic stability, durability and damage tolerance of concrete materials.

[0003] Traditional super high performance concrete has a microstructure mainly composed of closely packed cement-based materials, and lacks an effective mechanism for dissipating vibration energy. When subjected to high-frequency or repeated vibrations, stress concentration easily leads to rapid expansion of microcracks. After these microcracks are interconnected, the carrying capacity and durability of the material are significantly reduced. Therefore, although traditional super high performance concrete has good mechanical properties, its damping performance is poor, which ultimately threatens the safety and stability of the entire engineering structure. SUMMARY

[0004] The application aims to overcome the defects of super high performance concrete in extreme vibrating environments, such as poor damping performance, brittleness and easy fatigue failure, and provides a super high performance concrete suitable for a vibrating environment and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the application provides the following technical solutions.

[0006] A super high performance concrete suitable for a vibrating environment, characterized in that it comprises a reference component, an A component and a B component.

[0007] The reference component has a mass ratio of cement:silica fume:quartz sand:water reducing agent:water = 65-75:18-22:90-110:2-3:17-19.

[0008] The volume content of the A component is 1.0-2.0% of the total volume of the super high performance concrete.

[0009] The volume content of the B component is 2.5-4.0 times the volume of the A component.

[0010] Further, the super high performance concrete suitable for a vibrating environment, the cement is Portland cement, the particle size of the quartz sand is 0.1-0.3mm, and the water reducing agent is a polycarboxylate-based water reducing agent.

[0011] Further, the super high performance concrete suitable for a vibrating environment, the A component is prepared by the following steps:

[0012] (a) Alloy smelting: industrial pure iron, electrolytic manganese, crystalline silicon and micro-carbon chromium iron are put into a medium-frequency induction furnace, and the Fe-Mn-Si-Cr alloy liquid is smelted at 1580-1620℃ under argon protection, and then cast into wire rod, the alloy liquid is 15-18% of Mn, 4-6% of Si, 0.5-1.0% of Cr, and the balance of Fe in terms of mass ratio;

[0013] (b) Hot mechanical treatment: the wire rod is heated to 950℃ and kept for 30min, then air-cooled, and then tempered at 550℃ for 2h to obtain a hot mechanical treatment wire rod;

[0014] (c) Drawing: the hot mechanical treatment wire rod is drawn by using a straight-line drawing machine to a diameter of 0.2-0.5mm to obtain alloy fiber bare wire, the pass deformation is 15-18%, and the drawing speed is 80-120m / min;

[0015] By high-speed drawing, significant temperature rise effect can be generated by deformation heat and friction heat, which can induce dynamic recovery of Fe-Mn-Si alloy, partially offset the work hardening effect, soften the material, and thus allow greater deformation without cracking;

[0016] (d) Online coating: the alloy fiber bare wire immediately enters a crosshead die, the die temperature is 110℃, a single-component hot-melt epoxy resin stick is melted at 110℃, and is continuously extruded into the crosshead die through an extruder, and is uniformly coated on the surface of the running alloy fiber at the outlet of the die to form a continuous sheath layer with a thickness of 15-30μm, to obtain epoxy-coated alloy fiber;

[0017] (e) Online curing: the epoxy-coated alloy fiber directly passes through a UV-LED curing channel with a power density of 800-1000mW / cm2, a wavelength of 365nm, and a curing time of 3-5s, and is wound to obtain continuous fiber;

[0018] (f) Fiber shortening: the continuous fiber is processed by a fixed-length cutting machine to obtain short fibers with a length of 12-24mm, i.e. component A.

[0019] Further, the ultra-high performance concrete suitable for a vibrating environment is prepared by the following steps:

[0020] 1) Pre-emulsification: under room temperature, high-shear dispersion machine 8000-10000rpm, rotor linear speed 25-30m / s, the oil phase is dropped into the water phase at a flow rate of 50-80mL / min for 30min to obtain a stable pre-emulsion;

[0021] The oil phase mass ratio: butyl acrylate: styrene: glycidyl methacrylate: dimethylaminoethyl methacrylate: hydroxyethyl acrylate = 40-50: 10-15: 5-8: 3-5: 2-3, the water phase mass ratio: deionized water: anionic emulsifier: nonionic emulsifier = 50-60: 1-2: 0.5-1;

[0022] 2) Epoxy-amine modification: Dissolve isophorone diamine and glycidyl methacrylate in deionized water according to the molar ratio of epoxy group to primary amine hydrogen 1:1.1-1.3, prepare an amine solution with isophorone diamine mass fraction of 10%, add 5wt% sodium bicarbonate to maintain the pH of the amine solution at 8.5-9.0, add the amine solution to the stable pre-emulsion at a rate of 2-4mL / min under anchor stirring at 70-75℃ and 200-300rpm, the total drop time is 1-2h, and the reaction is maintained for 2-3h, the total amount of the amine solution added accounts for 5%-15% of the total mass of the stable pre-emulsion;

[0023] 3) Emulsion polymerization: Transfer the system of step 2) into a glass reaction kettle, four-fluorine anchor stirring, rotation speed 150-200rpm, temperature rise to 80-85℃, prepare a 2wt% ammonium persulfate solution, its dosage accounts for 0.4%-0.6% of the total mass of the pre-emulsion oil phase, drop at a constant pressure through a dropping funnel for 3-4h, maintain the reaction for 3-4h, cool down to 40℃ after the reaction is completed, adjust the pH to 7-8 with glacial acetic acid, add tert-butyl hydroperoxide 0.03-0.05% and sodium formaldehyde sulfoxylate 0.03-0.05% based on the total mass of the pre-emulsion, mature at 60℃ for 30min, and discharge to obtain component B.

[0024] Further, the preparation method of the ultra-high performance concrete suitable for a vibrating environment comprises the following steps:

[0025] S1: Dry mixing: Put cement, silica fume and quartz sand into a forced planetary mixer, with a revolution speed of 40rpm and a rotation speed of 80rpm, dry mix for 1-2min to obtain dry mixed material;

[0026] S2: Add component A: Put component A into the dry mixed material, continue to stir at low speed for 2-3min to obtain mixed dry mixed material;

[0027] S3: Prepare liquid phase: Put component B and water reducing agent into a high-speed disperser, disperse at 10000rpm for 1-2min to form a uniform liquid phase;

[0028] S4: Wet mixing and chemical bonding: Add the uniform liquid phase to the mixed dry mixed material at a rate of 2-3kg / min, switch to high-speed revolution of 60rpm and high-speed rotation of 120rpm, continue for 3-5min, control the discharge temperature at 20-25℃, and obtain the ultra-high performance concrete;

[0029] S5: pouring and curing: the ultra-high performance concrete is poured on a vibration table with a frequency of 50 Hz, an amplitude of 0.5 mm, and a vibration time of 30-60 s, and then is subjected to standard curing or steam curing.

[0030] Further, the ultra-high performance concrete is applied as an anti-vibration structural material in nuclear power facility foundations, precision instrument platforms, large-span bridge seismic components, high-speed railway sleepers, or military protection structures.

[0031] Compared with the prior art, the present application has the following beneficial effects:

[0032] 1. In the present application, a synergistic system of macro energy consumption and micro damping is constructed by components A and B. Component A is a Fe-Mn-Si shape memory alloy that provides active energy consumption and self-repairing ability under vibration load. The parameter design of 0.2-0.5 mm diameter and 15-30 μm sheath thickness not only ensures a mechanical strength of more than 800 MPa, but also reserves sufficient sites for interface reaction. Component B is an acrylate emulsion modified by epoxy-amine and containing primary amino groups, which is added in a solid volume of 2.5-4.0 times the volume of component A. The glass transition temperature of 0-20 ℃ ensures high damping characteristics at room temperature, and the solid content of 50-60% balances the fluidity and strength contribution. The adaptation of the two components with the reference component realizes the unity of high strength, high toughness and high damping from the material system level, and solves the problem that the damping performance and mechanical performance of traditional ultra-high performance concrete are difficult to balance.

[0033] 2. In the present application, through the ring-opening addition reaction of the epoxy groups in the sheath of component A and the amino groups in component B, a hydrolysis-resistant beta-hydroxylamine covalent bonding interface is formed, which has a bonding strength greater than physical adsorption, and realizes the transfer of energy between the fiber and the matrix. When vibrating, component B first dissipates the initial energy through molecular chain friction, and component A then inhibits crack propagation and consumes energy again by means of phase change restoring force, thereby synergistically improving the fatigue resistance. The volume fraction of component A is 1.0-2.0%, and the mixing is carried out in an alkaline environment, which not only avoids fiber clumping and excessive dilution of the strength of the emulsion, but also ensures the sufficiency of the interface reaction. The effect of gradient energy consumption is achieved through chemical bonding, so that the concrete has excellent dynamic stability and durability in extreme vibration environments such as nuclear power facilities and high-speed railway sleepers. BRIEF DESCRIPTION OF DRAWINGS

[0034] Figure 1 A flow chart for preparing the ultra-high performance concrete suitable for vibration environments. DETAILED DESCRIPTION

[0035] The technical solutions in the experiments of the present application will be clearly and completely described below in combination with the experiments of the present application. Obviously, the described experiments are only a part of the experiments of the present application, rather than all the experiments. Based on the experiments in the present application, all the other experiments obtained by those skilled in the art without creative labor fall within the protection scope of the present application.

[0036] It should be noted that the raw materials used in the following experiments are all commercially available.

[0037] Example 1

[0038] Raw material ratio (per cubic meter of concrete):

[0039] Reference component: Portland cement 650 kg, silica fume 180 kg, quartz sand with particle size of 0.1-0.3 mm 900 kg, polycarboxylic acid type water reducing agent 20 kg, water 170 kg;

[0040] A component: the volume content is 1.0% of the total volume of concrete, and the mass composition of the core material alloy is Mn: 15%, Cr: 0.5%, Fe: balance, the fiber diameter is 0.2 mm, and the thickness of the epoxy polymer sheath is 15 microns;

[0041] B component: the volume content is 2.5 times of the volume of A component;

[0042] Preparation method:

[0043] Preparation of A component:

[0044] (a) alloy smelting: industrial pure iron, electrolytic manganese, crystalline silicon and micro-carbon chromium iron are put into a medium-frequency induction furnace according to the ratio, and are smelted into alloy liquid at 1580℃ under argon protection, and are cast into wire rod;

[0045] (b) thermal mechanical treatment: the wire rod is heated to 940℃ and kept for 30 min, and then air-cooled, and then tempered at 540℃ for 2h;

[0046] (c) drawing: using a straight-line drawing machine, it is drawn to a diameter of 0.2mm in multiple passes, the pass deformation is 15%, and the drawing speed is 80m / min;

[0047] (d) online coating: the alloy fiber bare wire immediately enters a cross head mold, the mold temperature is 110℃, a single-component hot melt epoxy resin glue stick is melted at 110℃, and is continuously extruded into the cross head mold through an extruder, and is uniformly coated on the surface of the running alloy fiber at the outlet of the mold, forming a continuous sheath layer with a thickness of 15μm, to obtain an epoxy coated alloy fiber;

[0048] ​(e) Online curing: the epoxy-coated alloy fiber is directly cured by UV-LED curing channel, power density 800 mW / cm 2 , wavelength 365 nm, and the continuous fiber is obtained after winding after curing for 3 s;

[0049] (f) Fiber shortening: the continuous fiber is processed by a fixed-length cutting machine to obtain short fibers with a length of 12 mm, that is, the A component;

[0050] Preparation of the B component:

[0051] Pre-emulsification: at room temperature, the oil phase is dropped into the water phase at a flow rate of 50 mL / min under the action of a high-shear dispersion machine at 8000 rpm (rotor , linear speed 25 m / s) for 30 min to obtain a stable pre-emulsion;

[0052] Mass ratio of the oil phase: butyl acrylate: styrene: glycidyl methacrylate: dimethylaminoethyl methacrylate: hydroxyethyl acrylate = 40:10:5:3:2;

[0053] Mass ratio of the water phase: deionized water: sodium allyloxy hydroxypropyl sulfonate: octylphenol polyoxyethylene ether = 50:1:0.5;

[0054] Epoxy-amine modification: isophorone diamine and glycidyl methacrylate are dissolved in deionized water at a molar ratio of epoxy groups to primary amine hydrogen of 1:1.1 to prepare an amine solution with a mass fraction of isophorone diamine of 10%, 5 wt% sodium bicarbonate is added to maintain a pH of 8.5, the amine solution is added to the pre-emulsion at a rate of 2 mL / min under the action of an anchor stirrer at 70°C and 200 rpm, the total drop time is 1 h, and the reaction is maintained for 2 h, the total amount of the amine solution added accounts for 5% of the total mass of the stable pre-emulsion;

[0055] Emulsion polymerization: the system is transferred into a glass reaction kettle (tetrafluoro anchor stirrer, rotation speed 150 rpm), heated to 80°C, and a 2 wt% aqueous solution of ammonium persulfate is prepared, the amount of which accounts for 0.4% of the total mass of the oil phase of the pre-emulsion based on the solid content of ammonium persulfate, and is added at a constant speed for 3 h, and the reaction is maintained for 3 h, then the temperature is lowered to 40°C, the pH is adjusted to 7 with glacial acetic acid, and 0.03% of tert-butyl hydroperoxide and 0.03% of sodium formaldehyde sulfoxylate are added (based on the total mass of the pre-emulsion), and the system is aged at 60°C for 30 min, and then discharged to obtain the B component;

[0056] Preparation of the ultra-high performance concrete:

[0057] S1 dry mixing: the cement, silica fume, and quartz sand are put into a forced planetary mixer, the revolution speed is 38 rpm, and the rotation speed is 75 rpm, and the dry mixing is performed for 1 min;

[0058] S2 adding the A component: the A component is added, and the low-speed stirring is continued for 2 min;

[0059] S3 Preparation of liquid phase: Put B component and water reducing agent into high-speed disperser, stir at 10000 rpm for 1 min;

[0060] S4 Wet mixing and chemical bonding: Add uniform liquid phase into dry mixing material at a rate of 2 kg / min, switch to high-speed revolution of 58 rpm and rotation of 115 rpm, continue for 3 min, and the discharge temperature is 20℃;

[0061] S5 Paving and curing: Pave under the frequency of 48 Hz, amplitude of 0.4 mm, and vibration time of 30 s, and standard curing.

[0062] Example 2

[0063] Raw material ratio (per cubic meter of concrete):

[0064] Reference component: Portland cement 700 kg, silica fume 200 kg, quartz sand with particle size of 0.1-0.3 mm 1000 kg, polycarboxylic acid type water reducing agent 25 kg, and water 180 kg;

[0065] A component: The volume content is 1.5% of the total volume of concrete, and the mass composition of the core material alloy is Mn: 16.5%, Cr: 0.75%, Fe: balance, fiber diameter 0.35 mm, and epoxy polymer sheath thickness 22 microns;

[0066] B component: The volume content is 3.2 times the volume of A component;

[0067] Preparation method:

[0068] Preparation of A component:

[0069] (a) Alloy smelting: Put industrial pure iron, electrolytic manganese, crystalline silicon, and micro-carbon chromium iron according to the ratio into a medium-frequency induction furnace, smelt into Fe-Mn-Si-Cr alloy liquid at 1600℃ under argon protection, and then cast into coiled wire;

[0070] (b) Thermal mechanical treatment: heat the coiled wire to 950℃ for 30 min and then air cool, and then temper at 550℃ for 2 h to obtain a thermal mechanical treatment coiled wire;

[0071] (c) Drawing: draw the thermal mechanical treatment coiled wire to a diameter of 0.35 mm using a straight-line drawing machine to obtain alloy fiber bare wire, the pass deformation is 17%, and the drawing speed is 100 m / min;

[0072] (d) Online coating: the alloy fiber bare wire immediately enters ​Crosshead die, die temperature 110℃, single-component hot-melt epoxy resin glue stick melted at 110℃, continuously extruded into the crosshead die through the extruder, uniformly coated on the surface of the running alloy fiber at the outlet of the die, forming a 22μm thick continuous sheath layer, obtaining the epoxy-coated alloy fiber;

[0073] (e) Online curing: the epoxy-coated alloy fiber directly passes through the UV-LED curing channel, power density 900mW / cm 2 , wavelength 365nm, and is wound after curing for 4s to obtain a continuous fiber;

[0074] (f) Fiber shortening: the continuous fiber is processed through a fixed-length cutting machine to obtain a short fiber with a length of 18mm, i.e. the A component;

[0075] Preparation of the B component:

[0076] Pre-emulsification: at room temperature, under high-shear dispersion at 9000rpm (rotor , linear speed 27m / s), the oil phase is dropped into the water phase at a flow rate of 65mL / min for 30min to obtain a stable pre-emulsion;

[0077] The mass ratio of the oil phase: butyl acrylate: styrene: glycidyl methacrylate: dimethylaminoethyl methacrylate: hydroxyethyl acrylate = 45:12:6:4:2.5;

[0078] The mass ratio of the water phase: deionized water: sodium allyloxy hydroxypropyl sulfonate: octylphenol polyoxyethylene ether = 55:1.5:0.8;

[0079] Epoxy-amine modification: isophorone diamine and glycidyl methacrylate are dissolved in deionized water at a molar ratio of epoxy group to primary amine hydrogen of 1:1.2 to prepare an amine solution with a mass fraction of isophorone diamine of 10%, 5wt% sodium bicarbonate is added to maintain the pH of the amine solution at 8.7, the amine solution is added to the pre-emulsion at a rate of 3mL / min under anchor stirring at 72℃ and 250rpm, the total dropping time is 1.5h, and the reaction is kept for 2.5h, the total amount of the amine solution added accounts for 10% of the total mass of the stable pre-emulsion;

[0080] Emulsion polymerization: the system of step 2) is transferred to a glass reaction kettle (tetrafluoro anchor stirring, speed 175rpm), heated to 82℃, and ammonium persulfate is prepared into a 2wt% aqueous solution, the amount of which accounts for 0.5% of the total mass of the pre-emulsion oil phase in terms of ammonium persulfate solid, and is dropped at a constant speed for 3.5h, and the reaction is kept for 3.5h, then the temperature is lowered to 40℃, the pH is adjusted to 7.5 with glacial acetic acid, 0.04% tert-butyl hydroperoxide and 0.04% formaldehyde sodium sulfite are added (based on the total mass of the pre-emulsion), and the temperature is raised to 60℃ for 30min, then the product is discharged to obtain the B component;

[0081] Preparation of ultra-high performance concrete:

[0082] S1: dry mixing: put cement, silica fume and quartz sand into a forced planetary mixer, with a revolution speed of 40 rpm and a rotation speed of 80 rpm, dry mixing for 1.5 min to obtain dry mixed materials;

[0083] S2: adding A component: put A component into the dry mixed materials, continue to stir at low speed for 2.5 min to obtain mixed dry mixed materials;

[0084] S3: preparing liquid phase: put B component and water reducing agent into a high-speed disperser, stir at 10000 rpm for 1.5 min to form a uniform liquid phase;

[0085] S4: wet mixing and chemical bonding: add the uniform liquid phase into the mixed dry mixed materials at a rate of 2.5 kg / min, switch to high-speed revolution of 60 rpm and rotation of 120 rpm, continue for 4 min, and control the temperature of the outflowing materials at 22℃ to obtain ultra-high performance concrete;

[0086] S5: pouring and curing: pour the concrete on a vibrating table at a frequency of 50 Hz and an amplitude of 0.5 mm, and vibrate for 45 s, and then perform standard curing.

[0087] Example 3

[0088] Raw material ratio (per cubic meter of concrete):

[0089] Reference component: Portland cement 750 kg, silica fume 220 kg, quartz sand with a particle size of 0.1-0.3 mm 1100 kg, polycarboxylic acid type water reducing agent 30 kg, and water 190 kg;

[0090] A component: the volume content is 2.0% of the total volume of the concrete, the mass composition of the core material alloy is Mn: 18%, Cr: 1.0%, Fe: balance, the fiber diameter is 0.5 mm, and the thickness of the epoxy polymer sheath is 30 microns;

[0091] B component: the volume content is 4.0 times that of the A component;

[0092] Preparation method:

[0093] Preparation of A component:

[0094] (a) alloy smelting: put industrial pure iron, electrolytic manganese, crystalline silicon and micro-carbon chromium iron into a medium-frequency induction furnace according to the ratio, smelt into Fe-Mn-Si-Cr alloy liquid at 1620℃ under argon protection, and then cast into wire rod;

[0095] ​(b) Thermomechanical treatment: The wire rod is heated to 960℃ and held for 30 minutes, then air cooled, and then tempered at 560℃ for 2 hours to obtain thermomechanically treated wire rod;

[0096] (c) Drawing: The thermomechanically treated wire rod is drawn to a diameter of 0.5 mm in multiple passes using a straight-line wire drawing machine to obtain bare alloy fiber filaments. The deformation per pass is 18%, and the drawing speed is 120 m / min.

[0097] (d) Online coating: The bare alloy fiber filaments are then immediately encapsulated. A crosshead die with a die temperature of 110℃ is used to melt a single-component hot-melt epoxy resin stick at 110℃. The stick is then continuously extruded into the crosshead die through an extruder and uniformly coated onto the surface of the running alloy fiber at the die exit, forming a 30μm thick continuous sheath layer to obtain epoxy-coated alloy fiber.

[0098] (e) Online curing: Epoxy-coated alloy fibers are directly cured through a UV-LED channel at a power density of 1000 mW / cm². 2 Continuous fibers were obtained by winding after curing at a wavelength of 365nm for 5 seconds.

[0099] (f) Fiber chopped: Continuous fibers are processed by a length-cutting machine to obtain short fibers with a length of 12-24 mm, which is component A;

[0100] Preparation of component B:

[0101] Pre-emulsification: at room temperature, high shear disperser 10000 rpm (rotor) At a linear velocity of 30 m / s, the oil phase was added dropwise to the aqueous phase at a flow rate of 80 mL / min for 30 min to obtain a stable preemulsion.

[0102] The oil phase mass ratio is: butyl acrylate: styrene: glycidyl methacrylate: dimethylaminoethyl methacrylate: hydroxyethyl acrylate = 50:15:8:5:3;

[0103] The mass ratio of the aqueous phase is: deionized water: sodium allyloxyhydroxypropyl sulfonate: octylphenol polyoxyethylene ether = 60:2:1;

[0104] Epoxy-amine modification: Isophorone diamine and glycidyl methacrylate were dissolved in deionized water at a molar ratio of epoxy group to primary amine hydrogen of 1:1.3 to prepare an amine solution with a mass fraction of 10% isophorone diamine. 5 wt% sodium bicarbonate was added to maintain the pH of the amine solution at 9.0. The amine solution was added dropwise to the preemulsion at 4 mL / min under anchor stirring at 75℃ and 300 rpm for a total dropwise addition time of 2 h. The reaction was kept at this temperature for 3 h. The total amount of the amine solution added accounted for 15% of the total mass of the stable preemulsion.

[0105] Emulsion polymerization: Transfer the system from step 2) into a glass reactor (PTFE anchor stirrer, 200 rpm), heat to 85°C, prepare a 2 wt% aqueous solution of ammonium persulfate, the amount of which is based on the solid mass of ammonium persulfate and accounts for 0.6% of the total mass of the pre-emulsion oil phase, add it dropwise at a uniform rate over 4 hours, keep the reaction temperature for 4 hours, cool down to 40°C after the reaction is completed, adjust the pH to 8 with glacial acetic acid, add 0.05% tert-butyl hydroperoxide and 0.05% sodium formaldehyde sulfoxylate (based on the total mass of the pre-emulsion), mature at 60°C for 30 minutes, and discharge to obtain component B;

[0106] Preparation of ultra-high performance concrete:

[0107] S1: Dry mixing: Put cement, silica fume and quartz sand into a forced planetary mixer, with a revolution speed of 42 rpm and a rotation speed of 85 rpm, and dry mix for 2 minutes to obtain dry mix material;

[0108] S2: Add component A: Add component A to the dry mix and continue stirring at low speed for 3 minutes to obtain the mixed dry mix;

[0109] S3: Preparation of liquid phase: Place component B and water-reducing agent in a high-speed disperser, stir at 10000 rpm for 2 min to form a homogeneous liquid phase;

[0110] S4: Wet mixing and chemical bonding: Add the homogeneous liquid phase to the dry mixture at a rate of 3 kg / min, switch to high speed revolution at 62 rpm and rotation at 125 rpm for 5 min, and control the discharge temperature at 25℃ to obtain ultra-high performance concrete.

[0111] S5: Pouring and curing: The concrete is poured at a vibration table with a frequency of 52Hz, an amplitude of 0.6mm, and a compaction time of 60s, and then cured according to standard.

[0112] Comparative Example 1

[0113] Raw material ratio (per cubic meter of concrete):

[0114] Reference components: 700 kg silicate cement, 200 kg silica fume, 1000 kg quartz sand, 25 kg polycarboxylate superplasticizer, and 180 kg water.

[0115] Component A: None;

[0116] Component B: None;

[0117] Preparation method:

[0118] S1 Dry Mixing: 40 rpm for revolution, 80 rpm for rotation, dry mix for 2 minutes;

[0119] S2 Add component A: If component A is not present, omit this step;

[0120] S3 Preparation of Liquid Phase: Mix water-reducing agent with water and stir for 1 min;

[0121] S4 Wet mixing: Add liquid phase, revolve at 60 rpm, rotate at 120 rpm, and stir for 4 minutes;

[0122] S5 pouring: vibration frequency 50Hz, amplitude 0.5mm, compaction 45s, standard curing.

[0123] Comparative Example 2

[0124] Raw material ratio (per cubic meter of concrete):

[0125] Reference components: 700 kg silicate cement, 200 kg silica fume, 1000 kg quartz sand, 25 kg polycarboxylate superplasticizer, and 180 kg water.

[0126] Component A: Ordinary Fe-Mn-Si shape memory alloy fiber (composition same as in Example 2), volume fraction 1.5%, diameter 0.35 mm, without epoxy sheath layer;

[0127] Component B: The volumetric addition is 3.2 times that of Component A, and it does not contain primary amino groups;

[0128] Adjustment: Total water consumption minus emulsion water content;

[0129] Preparation method:

[0130] S1: Dry mixing: Same as in Example 2;

[0131] S2: Add component A: Add ordinary fiber and stir at low speed for 3 minutes;

[0132] S3: Preparation of liquid phase: Stir the remaining water, ordinary emulsion and water-reducing agent at high speed for 2 minutes;

[0133] S4: Wet mixing: Add the liquid phase and stir at high speed for 4 minutes;

[0134] S5: Pouring: Same as in Example 2.

[0135] Comparative Example 3

[0136] Raw material ratio (per cubic meter of concrete):

[0137] Reference components: 700 kg silicate cement, 200 kg silica fume, 1000 kg quartz sand, 25 kg polycarboxylate superplasticizer, and 180 kg water.

[0138] Component A: Same as in Example 2;

[0139] Component B: The volumetric addition amount is 6.0 times that of Component A;

[0140] Adjustment: Total water consumption minus emulsion water content;

[0141] Preparation method: Same as in Example 2.

[0142] Performance testing: The high-toughness corrosion-resistant nickel-based alloys obtained in Examples 1, 2, 3, Comparative Examples 1, 2, and 3 were subjected to performance tests, and the test data are recorded in the table below:

[0143]

[0144] In the performance tests, the ultra-high performance concrete obtained from Examples 1, 2, 3, Comparative Examples 1, 2, and 3 were tested. The compressive strength test was conducted in accordance with GB / T 50081-2019, the flexural strength test was conducted in accordance with GB / T 17671-2021, the flexural toughness test was conducted in accordance with GB / T 50080-2016, the damping characteristic test was conducted in accordance with GB / T19875-2005, the fatigue life test was conducted in accordance with GB / T 50476-2019, and the crack self-healing rate test was conducted in accordance with GB18445-2012.

[0145] As can be seen, Examples 1-3 all exhibited excellent mechanical properties. Comparative Example 1 had the lowest flexural strength and toughness due to the lack of fiber reinforcement. Comparative Example 2 had significantly lower flexural strength and toughness than Example 2 with the same ratio due to the lack of chemical bonding and weak interface. Comparative Example 3 had the lowest compressive and flexural strength due to the excessive emulsion damaging the water-cement ratio and matrix structure.

[0146] The high toughness index and ultra-long fatigue life of Examples 1-3 are due to the bridging, phase transformation superelasticity and strong chemical bonding interface between the A component shape memory alloy fiber and the matrix, which can effectively inhibit crack propagation. The physical bonding interface of Comparative Example 2 is prone to failure under cyclic loading, and its fatigue life is much lower than that of Example 2. The matrix strength of Comparative Example 3 is weakened, resulting in a shorter fatigue life.

[0147] Examples 1-3 achieved a balance between high damping and high strength through the gradient energy dissipation mechanism of the damping layer of component B and the energy-dissipating fiber of component A. Comparative Example 2 had limited damping performance due to low interfacial energy transfer efficiency. Although Comparative Example 3 had the highest damping ratio, this was achieved by relying on excessive soft polymer, which led to serious deterioration of mechanical properties.

[0148] The shape memory alloy fibers in Examples 1-3 generate restoring force under stress or temperature triggering, which can effectively close cracks and exhibit significant self-healing properties. The ordinary fibers in Comparative Example 2 do not have this function and have an extremely low repair rate. Although the fibers in Comparative Example 3 have this function, it is hampered by the deteriorated matrix. The data of Comparative Example 3 especially proves that there is an optimal range for the amount of component B added, rather than the more the better.

[0149] This invention, through the functional design and chemical bonding of components A and B, successfully prepared ultra-high performance concrete with optimal comprehensive performance, achieving a perfect combination of high strength, high toughness, high damping, and self-healing ability, far superior to various incomplete comparative schemes. Therefore, the ultra-high performance concrete suitable for vibration environments, its preparation method, and its application provided by this invention have a broader market prospect and are more suitable for promotion.

[0150] In the description of this specification, references to terms such as "an experiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that experiment or example is included in at least one experiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same experiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more experiments or examples.

[0151] The preferred experiments disclosed above are merely illustrative of the invention. These preferred experiments do not exhaustively describe all details, nor do they limit the invention to the specific embodiments described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these experiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize it. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-performance concrete suitable for vibration environments, characterized in that, Includes the reference component, component A, and component B; The reference components are in the following mass ratio: cement: silica fume: quartz sand: water-reducing agent: water = 65-75: 18-22: 90-110: 2-3: 17-19; The volumetric dosage of component A is 1.0%-2.0% of the total volume of the ultra-high performance concrete; Component A is prepared through the following steps: (a) Alloy smelting: Industrial pure iron, electrolytic manganese, crystalline silicon and micro-carbon ferrochrome are put into a medium frequency induction furnace and smelted into Fe-Mn-Si-Cr alloy liquid at 1580-1620℃ under argon protection, and then cast into φ8mm wire rod. (b) Thermomechanical treatment: The wire rod is heated to 950°C and held for 30 minutes, then air cooled, and then tempered at 550°C for 2 hours to obtain thermomechanically treated wire rod. (c) Drawing: The thermomechanically treated wire rod is drawn in multiple passes using a straight-line drawing machine to a diameter of 0.2-0.5 mm to obtain bare alloy fiber filaments; (d) Online coating: The bare alloy fiber filaments are then fed into a φ30mm crosshead die at a die temperature of 110℃. The single-component hot melt epoxy resin rod is melted at 110℃ and continuously extruded into the crosshead die through an extruder. It is uniformly coated on the surface of the running alloy fiber at the die exit to form a continuous sheath layer of 15–30μm thickness, thus obtaining epoxy-coated alloy fiber. (e) Online curing: Epoxy-coated alloy fibers are directly cured through a UV-LED channel, with a power density of 800-1000 mW / cm². 2 Continuous fibers are obtained by curing at a wavelength of 365nm for 3-5 seconds and then winding them up. (f) Fiber chopped short: Continuous fibers are processed by a length-cutting machine to obtain short fibers with a length of 12-24 mm, which is component A; The volumetric dosage of component B is 2.5-4.0 times that of component A; Component B is prepared through the following steps: 1) Pre-emulsification: At room temperature, under the conditions of a high shear disperser at 8000-10000 rpm, rotor φ30mm, and linear velocity of 25-30m / s, the oil phase is dropped into the aqueous phase at a flow rate of 50-80mL / min for 30min to obtain a stable pre-emulsion. 2) Epoxy-amine modification: Isophorone diamine and glycidyl methacrylate are dissolved in deionized water at a molar ratio of epoxy group to primary amine hydrogen of 1:1.1-1.3 to prepare an amine solution with a mass fraction of 10% isophorone diamine. 5 wt% sodium bicarbonate is added to maintain the pH of the amine solution at 8.5-9.

0. The amine solution is added dropwise to the stable preemulsion at 2-4 mL / min under anchor stirring at 70-75℃ and 200-300 rpm for a total dropwise addition time of 1-2 h. The reaction is maintained at this temperature for 2-3 h. The total amount of the amine solution added accounts for 5%-15% of the total mass of the stable preemulsion. 3) Emulsion polymerization: Transfer the system from step 2) into a glass reactor, stir with a PTFE anchor at 150-200 rpm, heat to 80-85℃, prepare a 2wt% aqueous solution of ammonium persulfate, the amount of which, based on the amount of solid ammonium persulfate, accounts for 0.4%-0.6% of the total mass of the pre-emulsion oil phase, and add it dropwise at a constant pressure dropping funnel over 3-4 hours. Keep the reaction at this temperature for 3-4 hours, and after the reaction is complete, cool to 40℃, adjust the pH to 7-8 with glacial acetic acid, and add 0.03-0.05% tert-butyl hydroperoxide and 0.03-0.05% sodium formaldehyde sulfoxylate based on the total mass of the pre-emulsion. Cure at 60℃ for 30 minutes, and discharge to obtain component B; The raw material mass ratio of the oil phase is: butyl acrylate: styrene: glycidyl methacrylate: dimethylaminoethyl methacrylate: hydroxyethyl acrylate = 40-50: 10-15: 5-8: 3-5: 2-3, and the raw material mass ratio of the aqueous phase is: deionized water: anionic emulsifier: nonionic emulsifier = 50-60: 1-2: 0.5-1.

2. The ultra-high performance concrete suitable for vibration environments according to claim 1, characterized in that, The cement used is silicate cement.

3. The ultra-high performance concrete suitable for vibration environments according to claim 1, characterized in that, The quartz sand has a particle size of 0.1-0.3 mm, and the water-reducing agent is a polycarboxylate-based water-reducing agent.

4. The ultra-high performance concrete suitable for vibration environments according to claim 1, characterized in that, The alloy liquid composition in step (a) is as follows by mass percentage: Mn: 15-18%, Si: 4-6%, Cr: 0.5-1.0%, Fe: balance.

5. The ultra-high performance concrete suitable for vibration environments according to claim 1, characterized in that, In step (c), the deformation per pass during the drawing process is 15-18%, and the drawing speed is 80-120 m / min.

6. The method for preparing ultra-high performance concrete suitable for vibration environments according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Dry mixing: Put cement, silica fume and quartz sand into a forced planetary mixer, with a revolution speed of 40 rpm and a rotation speed of 80 rpm, and dry mix for 1-2 minutes to obtain dry mix material; S2: Add component A: Add component A to the dry mix and continue stirring at low speed for 2-3 minutes to obtain the mixed dry mix; S3: Preparation of liquid phase: Place component B and water-reducing agent in a high-speed disperser at 10,000 rpm for 1-2 minutes to form a homogeneous liquid phase; S4: Wet mixing and chemical bonding: Add the homogeneous liquid phase to the dry mixture at a rate of 2-3 kg / min, switch to high speed revolution at 60 rpm and rotation at 120 rpm, continue for 3-5 min, and control the discharge temperature at 20-25℃ to obtain ultra-high performance concrete. S5: Pouring and Curing: The ultra-high performance concrete is poured at a vibration table frequency of 50Hz, amplitude of 0.5mm, and compaction time of 30-60s, followed by standard curing or steam curing.

7. The ultra-high performance concrete suitable for vibration environments prepared by the preparation method of the ultra-high performance concrete suitable for vibration environments according to claim 6 can be used as a vibration-resistant structural material in nuclear power facility foundations, precision instrument platforms, seismic components of long-span bridges, high-speed railway sleepers, or military protective structures.

Citation Information

Patent Citations

  • Cement-based composite material for steel box girder bridge deck, as well as preparation and pavement thereof

    CN103449786A

  • Self-repairing fiber-reinforced ultra-high performance concrete electrical pole and processing method thereof

    CN113045266A